2011
DOI: 10.2174/138161211795656954
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Aspects in Primary and Secondary Prevention of Cardiovascular Disease

Abstract: Gender differences in biological substrates of disease determine different clinical manifestations of CV disease with important implications for prevention, diagnosis and therapy in the two sexes. In women, the activity of sex hormones reduces the influence of CV risk factors during the reproductive age, and delays the onset of CHD of 2 decades compared to men. However, women as men suffer from CV events, and in women mortality from all CV causes and have greater than the sum of the others 7 causes of death to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 66 publications
0
15
0
1
Order By: Relevance
“…It is well known that premenopausal women are less likely to develop coronary heart disease than men of the same age and that heart failure appears to be less common and less severe in premenopausal women than in men 1 . Although previous studies have shown post-MI gender differences in LV remodeling, the data are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that premenopausal women are less likely to develop coronary heart disease than men of the same age and that heart failure appears to be less common and less severe in premenopausal women than in men 1 . Although previous studies have shown post-MI gender differences in LV remodeling, the data are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that premenopausal women have a lower risk of cardiovascular disease than men of the same age 1 . However, there are conflicting data about gender differences with regard to the adaptive response of the heart during the development of heart failure after myocardial infarction (MI).…”
Section: Introductionmentioning
confidence: 99%
“…2). However, women are more likely than men to die of a first myocardial infarction [34]. The levels of lipid components vary in different ages of life and in the two genders.…”
Section: Special Attention To Defined Risk Factors In Women At Least mentioning
confidence: 99%
“…For women with evidence of ischemia but non-obstructive CAD, antianginal and anti-ischemic therapies can improve symptoms, endothelial function, and quality of life; however, there is a great need of trials evaluating impact on adverse outcomes [23] although extremely large numbers are to be accrued for benefits around 10% [5] which demands for large multicentric cooperation in times of budget restrictions. Continued research is indicated to devise therapeutic regimens to improve symptom burden and reduce risk in women with ischemic heart disease and certainly both more conventional and unconventional strategies might deserve attention [29-34]. …”
Section: Introductionmentioning
confidence: 99%
“…In den letzten Jahren richtete sich das Augenmerk der biomedizinischen, präklini-schen und klinischen Forschung zunehmend auf geschlechtsspezifi sche Unterschiede (Mercuro et al 2010;Mercuro et al 2011;Picci et al 2012). Hier steht allerdings in erster Linie das biologische Geschlecht (Mann, Frau) im Vordergrund, weniger das soziale Geschlecht, also die soziokulturellen Rollen, die zusätzlich durch Faktoren wie ethnische Zugehörigkeit und Kultur sowie die soziale Schicht beeinfl usst werden (im Englischen "Gender").…”
Section: Introductionunclassified